2013
DOI: 10.3724/sp.j.1006.2012.00675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tillage Regimes on Water Consumption and Dry Matter Accumulation in Dryland Wheat

Abstract: The area of dryland wheat is large in Huang-Huai-Hai Rivers region, where grain yield of wheat was low and unstable because of deficient and variable precipitation. Conservation tillage is an important cultivation mode to stimulate crop production and has been a hotspot in cultivation research of winter wheat. Minimum tillage and no-tillage are believed to significantly increase grain yield and water use efficiency of dryland wheat. A field experiment was conducted to study the effects of tillage modes on wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Fertilizers constitute an integral part of improved crop production technology. Nitrogen (N) is an essential mineral nutrient for plant growth, expands soil fertility and crop productivity (López-Bellido et al 2012, Wang et al 2012. A proper amount of N fertilizer application is considered a key for high crop production (Liang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilizers constitute an integral part of improved crop production technology. Nitrogen (N) is an essential mineral nutrient for plant growth, expands soil fertility and crop productivity (López-Bellido et al 2012, Wang et al 2012. A proper amount of N fertilizer application is considered a key for high crop production (Liang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the length of time the NT process takes differs by region ( Boomsma et al, 2010 ). Wang et al (2012) showed that NT was beneficial to increasing the contents of soil aggregates, thereby increasing soil nutrients; however, it was suggested that years of NT would increase soil compactness and reduce crop yields. Here, NT resulted in the lowest maize yield and it was found that long-term NT could cause soil hardening and increases in bulk density ( Kan et al, 2020a ), affecting the development of crop root systems, as well as nutrient and water absorption, which may be why the lowest yields were recorded with NT in this study ( Ren et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The nitrogen accumulation in winter wheat under high N supply significantly exceeds the estimated sum of structural N and photosynthetic characteristics [30]. Showed that, under high nitrogen supply, the accumulation of above-ground nitrogen in winter wheat was as high as 5.1 kg ha −1 , which was more than 60% higher than the critical nitrogen concentration, indicating a high proportion of stored nitrogen in plants [31].Therefore, quantitative analysis of structural nitrogen, "photosynthetic characteristics, and nitrogen is of great significance for determining nitrogen accumulation and translocation in wheat plants. The results showed that compared to other in dryland wheat varieties, Yunhan-20410 had higher structural nitrogen (53.42 kg ha -1 on average), and Yunhan-618 had a higher structural nitrogen (50.47 kg ha -1 ), indicating that Yunhan-20410 had a higher structural nitrogen than other wheat varieties.…”
Section: Effects Of Differences Varieties Structural Nitrogen In Dryl...mentioning
confidence: 90%